2017
DOI: 10.1007/s10620-017-4470-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Insulin-PI3K/Akt-p70S6K Pathway in Hepatic Stellate Cells Contributes to Fibrosis in Nonalcoholic Steatohepatitis

Abstract: The insulin-PI3K/Akt-p70S6K pathway plays an important role in the early activation of HSC. The profibrogenic effect of insulin is dependent on the activation stage of HSC. Dysregulation of the insulin pathway likely correlates with the development of fibrosis in NASH, suggesting a potentially novel antifibrotic target of inhibiting insulin signaling in HSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 60 publications
4
35
0
Order By: Relevance
“…4A; ~ > 2 fold change in sh-PTEN knockdown cells with or without TGFβ1 vs sh-pLKO.1 control). Since AKT phosphorylation is directly linked to cell survival and activation of α-SMA in HSCs [3739]. We performed cell proliferation assays to determine whether knockdown of PTEN induced cell proliferation in LX-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…4A; ~ > 2 fold change in sh-PTEN knockdown cells with or without TGFβ1 vs sh-pLKO.1 control). Since AKT phosphorylation is directly linked to cell survival and activation of α-SMA in HSCs [3739]. We performed cell proliferation assays to determine whether knockdown of PTEN induced cell proliferation in LX-2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, GDF15 has been reported to induce phosphorylation of Akt and its downstream targets, c‐RAF and GSK‐3β . Insulin‐mediated activation of PI3K/Akt is also necessary for initial HSC activation . PI3K and ERK may in turn enhance SMAD binding under stressful conditions, via GDF15 secretion …”
Section: Discussionmentioning
confidence: 99%
“…The decrease of phosphorylated Akt, ERK, and JNK in the miR-6133-treated LX-2 cells could be due to the downregulation of FGFR1 , a target gene of miR-6133-5p. Several reports have shown that Akt is involved in collagen synthesis and the activation of HSCs [ 4 , 5 ]. JNK has also been reported to regulate collagen synthesis and the activation of HSCs [ 6 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, HSCs proliferate and differentiate into myofibroblasts and start to produce α-smooth muscle actin (α-SMA). Although extensive efforts have revealed that various signaling molecules such as Akt and c-Jun N-terminal kinase (JNK) control the activation and fibrogenesis of HSCs [ 4 , 5 , 6 , 7 , 8 ], the molecular processes involved in HSC activation are not entirely understood [ 9 ].…”
Section: Introductionmentioning
confidence: 99%